Management Earning Forecast dan Analyst Forecast : Sebuah Studi Meta Analysis - Karen Priscilla Wibowo; Vena Purnamasari (Owner : Riset dan Jurnal Akuntansi, 2023)
Management earnings forecast (MEF) is information that is needed by users of accounting information, therefore MEF must be precise and transparent so that it is relevant for decision making. An analyst also relies on MEF as one of the information as a basis for making the right estimate. MEF's research on forecasting corporate earnings by analysts is carried out in various industries, so a meta-analysis is needed to prove whether management's earnings forecasts consistently affect analysts' forecasts. The sample in this study are 8 journals that discuss management earnings forecasts on analyst forecasts from 1987 to 2020. The results of the heterogeneity test with meta-analysis show a p-value of 0.013, which means that the sampling error is relatively high. The results of the correlation analysis calculations show a p-value of 0.012 which means that the MEF in analyst forecasts is heterogeneous. Heterogeneous research results are caused by differences in the samples used in the study. Some studies use quarterly reports as samples and some use annual reports as samples.